Diagnostic Dilemmas and Surgical Challenges in the Management of Soft-tissue Tumors Mimicking Ganglion Cysts in the Finger - Ahmet Rifat Dogramaci; Gökçe Yildiran; Zeliha Esin Çelik; Mustafa Sutcu; Zekeriya Tosun (Turkish Journal of Plastic Surgery, 2024)
Ganglion cysts are the most common soft-tissue tumors observed in the finger. Some tumors could be easily confused clinically with ganglion cysts due to their localization, mobility, shape, and being soft in nature. In this article, two cases of schwannoma and superficial acral myxoma that were clinically and radiologically confused with ganglion cysts are presented. Suspecting this tumor type in the preoperative diagnosis is essential to avoid unnecessary surgical approaches. Masses in close proximity to the nerve or nerve sheath are very important as they require preservation of the nerve during surgery. For these masses, surgeons should be prepared as these cases can have many intraoperative surprises in store.